A quantitative approach to investigate discontinuous precipitation on grain boundary of Ni-based single crystal superalloys. (February 2017) - Yu, Z.; Zheng, Y.; Feng, Q.
Abstract: We designed a [001] tilt grain boundary by self-diffusion bonding technique in a single crystal superalloy. The effects of the grain boundary plane as well as its misorientation on discontinuous precipitation (DP) were investigated quantitatively. The anisotropic formation of DP colonies was associated with the anisotropic mobility of grain boundary plane. The critical misorientation for DP transformation is in between 20 and 25° for SXG3 alloy. The method proposed in this work can be used to investigate the misorientation tolerance of grain boundaries that occurs during casting of single crystal turbine blade. Graphical abstract: